Study on Fiber Reinforced Polymer Reinforced Circle Column Subjected to Axial Compression - Hou, Min; Dong, Jiangfeng; Li, Lang; Yuan, Shucheng; Wang, Qingyuan (Asian Journal of Chemistry, 2014)
In order to further advance knowledge of recycled aggregate concrete, fifteen short basalt fiber recycled aggregate concrete columns were fabricated and then tested to investigate the effects of the load carrying capacity, deformability and stiffness of basalt fiber recycled aggregate concrete columns reinforced by carbon fiber reinforced polymer (CFRP) sheets. The results demonstrated that the short columns’ ultimate load carrying capacity and stiffness could be greatly increased by two reinforcing arrangements: full wrapping arrangement and partial wrapping arrangement. The results also showed that the greater the carbon fiber reinforced polymer reinforcing ratio, the higher the ultimate load carrying capacity and deformability. In addition, the stiffness of the strengthened basalt fiber columns is more significantly enhanced in the columns that have a full wrapping arrangement than those with only a partial wrapping. Finally, the results indicated that the number of carbon fiber reinforced polymer significantly influences the load carrying capacity of the steel basalt fiber recycled aggregate concrete columns.